Hubungan Keterampilan Proses Sains dengan Keterampilan Berpikir Kritis pada Siswa SMPN Tindaret - Bansalina Salomina Rumbarak; Nancy Susianna; Nerru Pranuta Murnaka (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
Twenty-first-century education requires students to possess critical thinking abilities and science process skills in order to respond to the advancement of science and technology and to solve problems scientifically and systematically. Empirical conditions in schools indicate that junior high school students’ critical thinking skills remain relatively low because science learning is still predominantly teacher-centered and insufficiently engages students in scientific investigation activities. This study aimed to determine the relationship between science process skills and the critical thinking skills of eighth-grade students at SMP Negeri Tindaret on the topic of the human excretory system. The study employed a quantitative approach with a correlational research design. The research sample consisted of 25 students selected through purposive sampling techniques. Data were collected using a critical thinking skills test and an observation sheet assessing science process skills. Data analysis was conducted using descriptive statistics and the Pearson Product-Moment correlation test. The findings revealed that students’ critical thinking skills obtained a mean score of 75.80, while science process skills achieved a mean score of 73.00, both categorized as fairly good to high. The correlation analysis produced a coefficient value of 0.732 with a significance level of 0.000, indicating a strong and significant positive relationship between science process skills and students’ critical thinking skills. The findings further demonstrated that students who actively engaged in observation, experimentation, data processing, and scientific communication exhibited better analytical abilities and conclusion-drawing skills. The novelty of this study lies in revealing the empirical relationship between science process skills and critical thinking skills specifically in the topic of the human excretory system at SMP Negeri Tindaret, as well as in providing recommendations for science learning based on scientific investigation to strengthen students’ higher-order thinking skills in the twenty-first century.